Reflections and Proposals on the New Community Regulation on Public Procurement - Gimeno Feliú, José María (2015)
The article provides introductory notions about the new regulatory framework of the European Union on public procurement. The author argues that this new legislation forces us to rethink how articulate it to satisfies the public interest with respect to the principles of equality, efficiency, transparency, efficiency and accountability. It also forces us to rethink the administrative organization in the light of the own principles of public law. All that with the objective to approach us to the paradigm of the right to good administration as an element of control and accountability.